Development of a Cushion-Shaped Device to Induce Respiratory Rhythm and Depth for Enhanced Relaxation and Improved Cognition - Ban, Yuki; Karasawa, Hiroyuki; Fukui, Rui; Warisawa, Shin'ichi (Frontiers in Computer Science, 2022)
Workplace stress is a pertinent problem in today’s world. Since it is correlated with many health issues and can also lead to poor work performance, preventing and overcoming stress is a vital part of a healthy lifestyle. One of the most effective ways to promote relaxation is to control your breathing. However, regulating one's breathing requires a certain type of training, and it is not something that everyone can do easily. Therefore, we focused on the relaxation effect of respiration, and developed a cushion-shaped device that presents the target respiratory motion. We utilized the effect of inducing one's own respiratory movements through the respiratory movements of others. This device modified the user's respiratory rhythm and depth of the user when they hug it. We conducted a user study with this device, which revealed that presenting respiratory motion using our device can induce the user's respiratory rhythm and depth without any pre-training. In addition, subjective evaluation and ECG information suggested that using this device during breaks between tasks can enhance the relaxation effect and thus improve task performance after the break.